Communicating Globally / An Integrated Marketing Approach - Kitchen Philip J; Schultz Don E; Macmillan Business (2000)
This book offers a practitioner's perspective on integrated global marketing communication (IGMC) in action with vignettes, four complete case studies of well-recognized multinational brands, and one study case. Transitioning into the 21st-Century Marketplace, Understanding the Emerging Global Marketplace, How Marketing Communication Works, Integrated Communication or Integrated Marketing Communication, Developing Integrated Global Marketing Communication Programs, Implementing the IGMC Strategy, From Strategy to Creative Execution: Capturing the Imagination of Consumers and Publics, IGMC Drivers and Agency Interaction, An Integrated View of IGMC Management and Vendor Compensation, Developing IGMC Investments and Measurements, The Way Forward: Overcoming Barriers with IGMC Solutions, Bibliography, Index.